Edukasi Personal Branding bagi Siswa SMA Carnegie Medan di Era Digital - Sjukun Sjukun; Wily Julitawaty; Fenny Fenny; Yusuf Taufik (Jurnal Pemberdayaan Masyarakat, 2025)
This community service activity focused on enhancing the understanding and skills of Carnegie High School students in Medan in building personal branding in the digital era. With the rapid development of technology and the dominance of social media in daily life, positive personal branding has become a crucial factor for individual success, both in education and future career prospects. This activity was implemented as a short 1-hour workshop adopting an interactive and participatory approach, involving 40 students from grades X and XI. The workshop included a material presentation session covering the definition, importance of self-image, and use of digital platforms, followed by practical exercises such as creating a "branding statement" and social media bio. Direct observation and evaluation through questionnaires showed high enthusiasm from the students. A total of 36 out of 40 students successfully crafted their branding statements, reflecting diverse interests and aspirations, such as the desire to be known as creative students in digital art or students with leadership qualities. This indicates that the concept of personal branding can be effectively understood and applied in a short time. The majority of students (90%) reported a good understanding of the material, and 93% felt the topic was highly relevant to their lives. Additionally, 88% of students felt more confident in presenting the best version of themselves digitally, demonstrating a new awareness of the importance of forming a positive self-image online